Elephantopus scaber Linn. Leaf Extract Sensitizes Doxorubicin in Inducing Apoptosis in HSC-3 Tongue Cancer Cells through Inhibiting Survivin Activity at Thr34 - Sandra, Ferry; Hayuningtyas, Ria Aryani; Ranggaini, Dewi; Pang, Tiffany; Scania, Alifah Evi; Lee, Kyung Hoon (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Previous research has demonstrated the effect of Elephantopus scaber Linn. leaf extract (ESLE) on various cancer cell lines. However, research on the effects of ESLE on oral squamous cell carcinoma (OSCC), especially tongue cancer, is still lacking. Moreover, the apoptotic mechanisms induced by ESLE are not well understood and require further exploration. Therefore, this study was conducted to investigate the effects of ESLE on cell viability and apoptosis in human squamous cell carcinoma (HSC)-3 tongue cancer cells.METHODS: HSC-3 cells were treated with varying concentrations of ESLE, doxorubicin, and a combination of both. Cell viability and apoptosis were assessed using MTT and Sub-G1 assays. The expression levels of survivin and its phosphorylated form at threonine (Thr)34 were evaluated using Western blot analysis.RESULTS: ESLE exhibited a concentration-dependent cytotoxic effect on HSC-3 cells in decreasing cell viability (Kruskal Wallis, p=0.001) and increasing apoptotic cells (ANOVA, p=0.001) significantly. When combined with doxorubicin, ESLE further enhanced the induction of apoptosis compared with doxorubicin alone. The combined treatment resulted in a decrease in the levels of phosphorylated survivin (p-Surv) Thr34, indicating the inhibition of survivin's anti-apoptotic function.CONCLUSION: ESLE significantly enhances the efficacy of doxorubicin, thereby sensitizing its ability to induce apoptosis in HSC-3 tongue cancer cells. This sensitization occurs through the inhibition of survivin activity, particularly at the Thr34 phosphorylation site. These findings suggest that ESLE could serve as a potential adjuvant to improve the effectiveness of doxorubicin in inducing apoptosis in tongue cancer cells.KEYWORDS: Elephantopus scaber, doxorubicin, tongue cancer, HSC-3 cells, apoptosis, Survivin, Thr34 phosphorylation